Mesenchymal stem cell-derived exosomes–a promising therapeutic approach to improve neurocognitive disorders in chronic obstructive pulmonary disease - Hui Xiao; Xiao Yu; Yushan Liu; Wenhua Jiang; Xiaoting Meng; Zhiyong Dong; Fang Wang (Stem Cell Research & Therapy)
Abstract Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide and is often accompanied by neurocognitive disorders. It seriously affects the quality of life and treatment outcome of patients. COPD-induced neurocognitive disorders (COPD-NCDs) are driven by systemic inflammation, blood-brain barrier (BBB) disruption, and chronic hypoxia, but there is currently no effective treatment to prevent or reverse cognitive decline. Mesenchymal stem cell-derived exosomes (MSC-Exos) are nanoscale extracellular vesicles with unique bioactivity, which have shown great potential in the fields of nervous system diseases, respiratory diseases, bone and joint diseases. Different from traditional cell therapies, MSC-Exos have the advantages of non-immunogenicity, non-tumorigenicity, high stability and biocompatibility. In addition, MSC-Exos can also cross the BBB, regulate neuroinflammation, promote neurogenesis, enhance myelination and improve synaptic plasticity, thereby addressing the multifaceted pathogenesis of central nervous system (CNS) diseases. In this review, we first summarize the pathogenic mechanism of COPD-NCDs, and then summarize the multiple mechanisms of MSC-Exos improving NCDs based on the efficacy of MSC-Exos on other CNS diseases, emphasizing the theoretical basis and unique potential of MSC-Exos as a treatment for COPD-NCDs. Finally, we prospected the future research directions and potential problems of applying MSC-Exos to treat COPD-NCDs, future research should focus on optimizing the large-scale preparation of MSC-Exos, exploring their long-term safety, and advancing clinical translation to address the unmet needs of COPD-NCDs patients.